2011
DOI: 10.1021/la203419y
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Chemistry of Capsular Assemblies in Aqueous Solution and on Silica Surfaces

Abstract: Synthesis and encapsulation properties of two new water-soluble resorcinol-capped organic cavitands (tetra acid and octa acid; RTA and ROA) are reported in this Letter. Organic guest molecules template the formation of capsular assembly of the above cavitands in water. Depending upon the guest, either 1:2 (guest to host) or 2:2 capsular assemblies were formed. The excited state properties of guests such as anthracene, camphorthione, and 4,4'-dimethyl benzil were distinctly different within a capsular assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…There was a kinetic likeness in the photorelease although the sigmoid was 7.7‐fold steeper in the n ‐butanol than the PBS. Silica surface properties and factors including greater solubility in n ‐butanol than PBS play key roles in the extent of the pheophorbide retention on the silica tip surface. The results were similar from internal irradiation (described here) vs external irradiation of the sensitizer solid, where increasing light intensity in the former was a correlation with, but not causation of the sigmoidal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…There was a kinetic likeness in the photorelease although the sigmoid was 7.7‐fold steeper in the n ‐butanol than the PBS. Silica surface properties and factors including greater solubility in n ‐butanol than PBS play key roles in the extent of the pheophorbide retention on the silica tip surface. The results were similar from internal irradiation (described here) vs external irradiation of the sensitizer solid, where increasing light intensity in the former was a correlation with, but not causation of the sigmoidal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…85 In addition to serving as solution-based reaction vessels, these types of cavitands have been immobilized on silica surfaces 86 and appended to gold nanoparticles. For example, azidoadamantanes form stable 1:1 complexes with OA 37, which upon irradiation result in the corresponding nitrene complexes in which the guest inserts into one of the four benzyl hydrogens of the host.…”
Section: Applicationsmentioning
confidence: 99%
“…128 They demonstrated that the properties of photo-reactor are maintained in the heterogeneous system, and that capsular assemblies are stable on silica surface.…”
Section: Metallo-cage Capsulesmentioning
confidence: 99%